Симультанні операції в хірургічному лікуванні хворих з ендокринною патологією - Завгородній, С. М.; Головко, М. Г.; Гайдаржі, Є. І.; Вільховой, С. О.; Русанов, І. В.; Децик, Д. А.; Доля, О. С.; Подлужний, О. О. (Clinical Endocrinology and Endocrine Surgery, 2009)
The results of surgical treatment of 24 patients with an endocrine pathology by which simultaneous operations have been executed are presented. Technical and tactical questions of similar operative technique are discussed. Advantages of single-step surgical correction of several endocrine diseases at one patient are shown. The received experience proves a possibility and expediency of performance of simultaneous operations at patients with combined endocrine pathology.